A comparative study on different types of metamaterials for enhancement of microstrip patch antenna directivity at the Ku-band (12 GHz) - Tutuncu, Bilal; Torpi, Hamid; Urul, Bulent (Tubitak Scientific & Technological Research Council Turkey, 2018)
This paper proposes improving the directivity of microstrip patch antennas (MPAs) by using metamaterials. Four different metamaterial types are used as a flat lens in front of the MPA, respectively, which are tuned to 12 GHz (Ku-band) resonance frequency. Thus, it can be decided which metamaterial is more proper for antenna directivity enhancement at this band. One additional new metamaterial structure is proposed in this paper, which is called a Euro-shaped resonator, and other metamaterials used are the triangular split ring resonator, symmetrical ring structure, and split ring resonator. The permeability and permittivity of metamaterials are extracted from the S parameters by using a robust method. Microwave Studio by Computer Simulation Technology is used for modeling and simulation. The MPA and metamaterials are fabricated, and measurements are performed in the Yildiz Technical University RF and Microwave Laboratory. It is observed that measured results are in close agreement with the computer simulations.
Keywords: Metamaterial; microstrip patch antenna; Ku-band; Euro-shaped resonator; triangular split ring resonator; symmetrical ring structure; split ring resonator; GAIN; Computer Science; Engineering